Respostas

2014-06-25T14:00:37-03:00
2014-06-25T14:02:44-03:00
2x ao quadrado -6x-2=0

2x² - 6x - 2 = 0
a = 2
b = - 6
c = -2
Δ = b² - 4ac
Δ = (-6)² - 4(2)(-2)
Δ = + 36 + 16
Δ = 52 ----------------fatrorar 52| 2
                                            26| 2
                                            13| 13
                                              1/
Δ = 52------------√52 = √2.2.13 = √2² . 13  = 2√13 

se 
Δ > 0  então 
(baskara)
x = - b - + 
√Δ/2a

x' = -(-6) - √52/2(2)
x' = + 6 - 2√13/4

            6  -  2√13   : 2            3 - √13
 x'=      --------------           = -------------- =  3-√13/2
                4           : 2                2


x" = -(-6) + √52/2(2)

x" = + 6 + 2√13/4

         6 + 2√13     : 2             3 + √13
x" = ------------------       =   ------------ =  3 + √13/2
             4             : 2                2